2007
DOI: 10.1179/crn.2007.029
|View full text |Cite
|
Sign up to set email alerts
|

Low Intensity Laser Application in Temporomandibular Disorders: A Phase I Double-Blind Study

Abstract: The purpose of this study was to evaluate the effectiveness of low intensity laser therapy (LILT) for the control of pain from temporomandibular disorder (TMD) in a random and double-blind research design. Forty-eight (48) patients presenting temporomandibular joint (TMJ) pain were divided into an experimental group (GI) and a placebo group (GII). The sample was submitted to the treatment with infrared laser (780 nm, 70 mW, 10 s, 89.7 J/cm2) applied in continuous mode on the affected temporomandibular region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
32

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 10 publications
4
116
1
32
Order By: Relevance
“…Some authors reported the efficacy of LLLT to be superior to placebo therapy [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and other physical therapies , while, others found no significant differences between LLLT and placebo for the measures of TMJ pain [24][25][26]. However there is an advantage of using LLLT in the treatment of TMDs as it is non-invasive, cost effective and does not have any known side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported the efficacy of LLLT to be superior to placebo therapy [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and other physical therapies , while, others found no significant differences between LLLT and placebo for the measures of TMJ pain [24][25][26]. However there is an advantage of using LLLT in the treatment of TMDs as it is non-invasive, cost effective and does not have any known side effects.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the 1990s, there was a small but steady increase, a development that has been accentuated in the last 10 years. according to phase I (Singh et al, 2008;Mazetto et al, 2007;Kim et al, 2004;Zeltzer et al, 2002), and another four according to phase II (Beer et al, 2010;Lansdown et al, 2009;Vickers et al, 2004;Wong et al, 2003). A relevant question is if this growth is larger than the general increase of published items on acupuncture?…”
Section: Clinical Trialsmentioning
confidence: 99%
“…A boa relação entre profissional e paciente, associados com aparência de alta tecnologia do laser, pode explicar a redução da sintomatologia dolorosa nos grupos que tiveram essa modalidade terapêutica para alívio de dor (Conti, 1997;Mazzetto et al, 2007; de Moraes-Maia et al, 2014).…”
Section: Tomados Em Conjunto Os Resultados Atuais Indicam Que O Protunclassified
“…A terapia com laser de baixa intensidade (LLLT), assim como a TMO, é um tratamento não invasivo que tem mostrado ser benéfico no tratamento de dor relacionado à DTM sendo, portanto, considerado eficiente como agente terapêutico e coadjuvante no tratamento das DTM (Kulekcioglu et al, 2003;De Medeiros et al, 2005;Çetineret al, 2006;Mcnelly et al, 2006;Medlicott e Harris, 2006;Shinozaki et al, 2006;Fikácková et al, 2007;Mazzetto et al, 2007;Carrasco et al, 2008;Shirani et al, 2009;Marini et al, 2010;Venezian et al, 2010;Mazzetto et al, 2010;Oz et al, 2010;Dostalová et al, 2012;Sattayut et al, 2012;de Moraes Maia et al, 2014;Salmos-Brito et al, 2013;Melchior et al, 2013;Ahrari et al, 2014;Herpich et al, 2015;Rodrigues et al, 2015).…”
Section: Tomados Em Conjunto Os Resultados Atuais Indicam Que O Protunclassified
See 1 more Smart Citation